Influence Of Class Climate Perception And Self-Efficacy On Student Engagement (A Case Study at Taruna Surabaya Shipbuilding Polytechnic) - Puspitacandri, Ardhiana; Soesatyo, Yoyok (Journal of Education, Health and Sport, 2019)
This study aims to determine the influence of class-climate perception and self-efficacy on student engagement. The method used was the quantitative correlational approach with the population was the 317 Diploma students of Shipbuilding Polytechnic Taruna Surabaya who program Construction Diploma.The results showed that: 1) there is an influence of the class-climate perception on student engagement in Shipbuilding Polytechnic Taruna Surabaya indicated by the value of t statistic was higher than t table (4.279 > 1.980) with a significant 0.000. It means that class-climate perception has a positive and significant relationship with student engagement (as 33.3%); 2) there is an influence of self-efficacy on Student Engagement in the Shipbuilding Polytechnic Taruna Surabaya indicated by the value of tstatistic was higher than t table (3.599 > 1.980) with a significant 0.000. It means that self-efficacy has a direct and significant relationship with student engagement (as 28.0%); and 3) there is a direct and simultaneous influence of both class-climate perception and self-efficacy on student engagement in Shipbuilding Polytechnic Taruna Surabaya indicated by the Fstatistic was higher than Ftable (14.574 > 2.68) with significance of 0.000. It means that there is a positive and direct relationship of class-climate perception and self-efficacy on student engagement. From the calculation indicated that class-climate perception and self-efficacy possibly change the value of student engagement as only 17.5%, while the remaining 82.5% was possibly due to other varibles excluding in this study.In conclusion, to make students actively involve in the class, it can be done by improving the class facilities and infrastructure. Praising and motivating students will grow their self-confidence, so students tend to be more persistant and unhesitant to answer adn fulfill the challenge/task given by teachers.